2023
DOI: 10.3389/fimmu.2023.1112196
|View full text |Cite
|
Sign up to set email alerts
|

The role of G protein-coupled receptor in neutrophil dysfunction during sepsis-induced acute respiratory distress syndrome

Abstract: Sepsis is defined as a life-threatening dysfunction due to a dysregulated host response to infection. It is a common and complex syndrome and is the leading cause of death in intensive care units. The lungs are most vulnerable to the challenge of sepsis, and the incidence of respiratory dysfunction has been reported to be up to 70%, in which neutrophils play a major role. Neutrophils are the first line of defense against infection, and they are regarded as the most responsive cells in sepsis. Normally, neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 349 publications
2
2
0
Order By: Relevance
“…Using the prognostic model, septic patients were divided into high-risk group and low-risk group to further study the different patterns of immune infiltration. Neutrophils and T cells exhibited higher scores within the high-risk group, consistent with prior investigations 22 , 40 . Several researches have been shown that neutrophil dysfunction stands as a pivotal contributor to multiple organ failure in sepsis, and the compromised migration of neutrophils bears direct implications for sepsis prognosis 40 43 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Using the prognostic model, septic patients were divided into high-risk group and low-risk group to further study the different patterns of immune infiltration. Neutrophils and T cells exhibited higher scores within the high-risk group, consistent with prior investigations 22 , 40 . Several researches have been shown that neutrophil dysfunction stands as a pivotal contributor to multiple organ failure in sepsis, and the compromised migration of neutrophils bears direct implications for sepsis prognosis 40 43 .…”
Section: Discussionsupporting
confidence: 90%
“…Neutrophils and T cells exhibited higher scores within the high-risk group, consistent with prior investigations 22 , 40 . Several researches have been shown that neutrophil dysfunction stands as a pivotal contributor to multiple organ failure in sepsis, and the compromised migration of neutrophils bears direct implications for sepsis prognosis 40 43 . Moreover, T cell-mediated immune responses also play a crucial role in sepsis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6 ). Additionally, the BINN highlighted several pathways with relevance to ARDS such as the G-coupled protein receptors-pathway 49 , which contributed to the Signal Transduction pathway as being one of the most important (Fig. 6) .…”
Section: Resultsmentioning
confidence: 99%
“…During sepsis, neutrophils are often the first immune cells to be recruited to infected sites [ 7 ]. Calprotectin (S100a8/a9), a heterodimeric Ca 2+ -binding protein mainly released by neutrophils, is thought to induce prolonged inflammation and endothelial injury through binding with its receptors, including toll-like receptor 4 (TLR4) and receptor for advanced glycation end products (RAGE) [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%